Grunnen til at retrofleks l snart er einerådande i hovudstaden Oslo - Håkon Jahr, Ernst (Scripta Neophilologica Posnaniensia, 2020)
This paper describes a sound change involving the lateral system in Oslo Norwegian from ca. 1880 till today. From an early (c. 1880) system comprised of mainly one dental (or alveolar) /l/ in all positions (except for an occasional retroflex [ɭ] for the assimilated cluster [rl]), the retroflex [ɭ] allophone spread during the 20th century to all phonological contexts except following an [a(:)] or [o(:)] in a stressed syllable. Jahr (1975, 1988) claimed that this situation would probably prevail, and the sound change would not be completed and yield a simpler system, because of the attitude of Oslo speakers towards a low-status dialect feature associated with an area southeast of the capital. However, around the turn of the millennium, the development towards a simple one /l/ allophone system nevertheless continued, and children throughout the city started using the retroflex [ɭ] also after [a(:)] and [o(:)]. The last leg of this very long development could be completed, the author claims, because a large region around the capital in the last 50 years has aquired an oral variety based in the capital, but the speakers of this region did not have the negative attitude of the Oslo speakers towards the low-status dialect southeast of Oslo (the Østfold dialect). Therefore, the ‘new’ speakers of the mainly Oslo dialect, from the region around the capital, did not copy the ‘strange’ Oslo exception of the lateral system after the vowels [a(:)] and [o(:)], and this over the years came to have decisive impact also on the speech of young speakers from Oslo itself.